Concurrent Infections of Porcine Circovirus 2 and Swinepox Virus in Crossbred Piglets - Sangavi, K. R.; Chaurasiya, Alok Kumar; Saran, M. E.; Singh, Deepti; Jana, C.; Pawaiya, R. V. S. (International Journal of Bio-resource and Stress Management, 2026)
The study was conducted during September and October, 2024 at a local farm in Bareilly, Uttar Pradesh, India to investigate the etiologies and pathology of concurrent viral infections in piglets. Post mortem examinations of three crossbred piglet carcasses (38-day-old male, 42-day-old female and 50-day-old female) were conducted having history of reduced feed intake, severe dullness, progressive lethargy, diarrhoea and multifocal cutaneous circumscribed scabs followed by death. Necropsy revealed pericarditis with serous fluid accumulation, pulmonary consolidation with edema, hepatic congestion and necrosis, intestinal lymph nodes congestion, renal tubular degeneration and characteristic cutaneous pock lesions with umbilicated crusts. Histopathology showed interstitial pneumonia, hepatic sinusoidal congestion, sloughing of intestinal villus epithelium, lymphoid depletion in lymph nodes and characteristic swine pox lesions like vacuolar degeneration of keratinocytes in the epidermis with eosinophilic intracytoplasmic inclusion bodies. All tissue samples from the three affected piglets were found to be positive for porcine circovirus 2 (PCV2) and swinepox virus (SWPV) by PCR amplification of ORF2 and P42 genes, respectively. Organ-wise viral distribution analysis revealed PCV2 predominantly in lymphoid tissues, heart and lungs, while SWPV was predominantly detected in skin and lymphoid tissues. Based on pathomorphological and molecular investigations, the cause of death of the piglets was diagnosed as concurrent infections of PCV2 and SWPV in piglets maintained under poor biosecurity conditions. PCV2-induced immunosuppression likely exacerbated swinepox severity through enhanced viral replication and systemic dissemination.